Air quality and waste management analysis of used ayurvedic oil in an off-road twin cylinder tractor engine - Balakumar Ranganathan; Sriram Gopalasamy; Arumugam Shanmugasundaram (International Journal of Sustainable Engineering, 2021)
Off-road diesel engines for genset applications, municipal and farming activities are the major contributors to harmful emissions. To address this, the present research reports the use of biodiesel derived from Waste Ayurvedic Oil (WAO) in an off-road twin cylinder compression ignition engine. The methyl ester of WAO was formulated using the ultrasound irradiated transesterification process. The different blends of WAO methyl ester and diesel, say WAO10, WAO15 and WAO20 were prepared and experimented on a Mahindra-Maximo twin cylinder tractor engine in order to analyse its performance, emission and combustion behaviour. As compared to diesel, WAO blends offer increased specific fuel consumption with comparable brake thermal efficiency for WAO10 over all the engine speeds. WAO10, WAO15 and WAO20 diminished CO emissions by 16.12%, 22.58% and 29.03%, HC emission by 19.04%, 42.8% and 61.9% as well as smoke opacity by 14.28%, 28.57% and 42.85% together with amplified NOx emission by 2.73%, 10.95% and 21.5% respectively in comparison with diesel. Therefore, WAO is a cost-effective feedstock for biodiesel synthesis, and its blends could be used as off-road diesel engine substitutes.